Pharmacokinetic interaction profile of riociguat, a new soluble guanylate cyclase stimulator, in vitro - Rickert-Zacharias, Verena Martina; Haefeli, Walter E.; Weiß, Johanna (Pulmonary pharmacology and therapeutics, 2014)
Riociguat is a new soluble guanylate cyclase stimulator under development for pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension. So far, the interaction potential of riociguat with other drugs is nearly unknown. Therefore, we assessed in vitro the potency of riociguat to inhibit important drug metabolising enzymes (cytochrome P450 (CYP) 3A4, CYP2C19, and CYP2D6) and drug transporters (P-glycoprotein (P-gp/ABCB1), breast cancer resistance protein (BCRP/ABCG2), and organic anion transporting polypeptides (OATP) 1B1 and 1B3). In addition we evaluated its substrate characteristics for P-gp, BCRP, and the multidrug resistance-associated protein 1 (MRP1/ABCC1). We also assessed riociguat's inducing properties on important drug metabolising enzymes and transporters and investigated its ability to activate the pregnane-X-receptor (PXR). Riociguat was identified as a weak to moderate inhibitor of P-gp (f2-value: 11.7 ± 4.8 μM), BCRP (IC50 = 46.2 ± 20.3 μM), OATP1B1 (IC50 = 34.1 ± 3.15 μM), OATP1B3 (IC50 = 50.3 ± 7.5 μM), CYP2D6 (IC50 = 12.4 ± 0.74 μM), and CYP2C19 (IC50 = 46.1 ± 7.14 μM). Furthermore, it induced mRNA expression of BCRP/ABCG2 (3-fold at 20 μM) and to a lesser extent of CYP3A4 (2.3-fold at 20 μM), UGT1A4, and ABCB11. The only weak inducing properties were confirmed by weak activation of PXR. Considering its systemic concentrations its interaction potential as a perpetrator drug seems to be low. In contrast, our data suggest that riociguat is a P-gp substrate and might therefore act as a victim drug when co-administered with strong P-gp inductors or inhibitors.